MOVAS C2009: DURUM WHEAT WITH RESISTACE TO STEM RUST - Félix-Fuentes, José Luis; Fuentes-Dávila, Guillermo; Figueroa-López, Pedro; Chávez-Villalba, Gabriela; Valenzuela- Herrera, Víctor; Mendoza-Lugo, José Alberto (Revista Mexicana de Ciencias Agrícolas, 2018)
The Movas C2009 variety was developed in the experimental field Norman E. Borlaug, in a collaborative project between INIFAP and CIMMYT, for the producing areas in the States of Sinaloa, Sonora and Baja California in Mexico. Its pedigree is CMH83.2578/4/D88059// WARD/YAV79/3/ACO89/5/2∗SOOTY-9/RASCON- 37/6/1A.1D5+106/3∗MOJO/3/AJAIA-12/F3LOCAL(SEL. ETHIO.135.85)//PLATA-13, and its selection history CDSS02B00720S-0Y-0M-8Y-1M-04Y-0B. Movas C2009 has a provisional registration, 2415-TRI-097-190410/C of the National Catalogue of Plant Varieties of the National Seed InspectionandCertificationService.Thisvarietyhasaspring- growth habit and is resistant to stem rust (Puccinia graminis f. sp. tritici) with an average grain yield of 6.35, 5.9 and 7.6 t ha-1 with two, three and four auxiliary irrigation, respectively; in four planting dates, being superior to the control Jupare C2001. In plots with cooperating farmers, Movas C2009 exceeded on average, the control in 0.5 t ha-1 in grain yield in six validations, so it represents a new option for durum wheat to farmers in the northwest.
Keywords: disease; improvement; resistance; yield